Design, Dynamics, and Workspace of a Hybrid-Driven-Based Cable Parallel Manipulator. (14th March 2013) - Zi, Bin; Cao, Jianbin; Zhu, Zhencai; Mitrouchev, Peter
Abstract : The design, dynamics, and workspace of a hybrid-driven-based cable parallel manipulator (HDCPM) are presented. The HDCPM is able to perform high efficiency, heavy load, and high-performance motion due to the advantages of both the cable parallel manipulator and the hybrid-driven planar five-bar mechanism. The design is performed according to theories of mechanism structure synthesis for cable parallel manipulators. The dynamic formulation of the HDCPM is established on the basis of Newton-Euler method. The workspace of the manipulator is analyzed additionally. As an example, a completely restrained HDCPM with 3 degrees of freedom is studied in simulation in order to verify the validity of the proposed design, workspace, and dynamic analysis. The simulation results, compared with the theoretical analysis, and the case study previously performed show that the manipulator design is reasonable and the mathematical models are correct, which provides the theoretical basis for future physical prototype and control system design.